Recent approaches towards bone tissue engineering - Maia, F. Raquel (2022)
Bone tissue engineering approaches have evolved towards addressing the challenges of tissue mimetic requirements over the years. Different strategies have been combining scaffolds, cells, and biologically active cues using a wide range of fabrication techniques, envisioning the mimicry of bone tissue. On the one hand, biomimetic scaffold-based strategies have been pursuing different biomaterials to produce scaffolds, combining with diverse and innovative fabrication strategies to mimic bone tissue better, surpassing bone grafts. On the other hand, biomimetic scaffold-free approaches mainly foresee replicating endochondral ossification, replacing hyaline cartilage with new bone. Finally, since bone tissue is highly vascularized, new strategies focused on developing pre-vascularized scaffolds or pre-vascularized cellular aggregates have been a motif of study. The recent biomimetic scaffold-based and scaffold-free approaches in bone tissue engineering, focusing on materials and fabrication methods used, are overviewed herein. The biomimetic vascularized approaches are also discussed, namely the development of pre-vascularized scaffolds and pre-vascularized cellular aggregates.